1994
DOI: 10.1037/0278-7393.20.4.934
|View full text |Cite
|
Sign up to set email alerts
|

Source misattributions and the suggestibility of eyewitness memory.

Abstract: Although the suggestibility of eyewitness memory is well documented, previous studies have not clearly established the extent to which misled Ss might come to believe they actually remember seeing the suggested details they report. To assess whether Ss confuse misleading suggestions for their "real memories" of a witnessed event, Ss were asked specific questions about their memory for the source of suggested items. The results of 5 experiments showed that misled Ss do sometimes come to believe they remember se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
310
2
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 277 publications
(331 citation statements)
references
References 45 publications
(78 reference statements)
18
310
2
1
Order By: Relevance
“…In Zaragoza and Lane's (1994) study, which was unsuccessful, the warning used terminology that indicated to the participants that they would definitely be exposed to material that contained misleading information. In our study, we used terminology that indicated to the participants that they "may" be exposed to material that contained misleading ·information.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Zaragoza and Lane's (1994) study, which was unsuccessful, the warning used terminology that indicated to the participants that they would definitely be exposed to material that contained misleading information. In our study, we used terminology that indicated to the participants that they "may" be exposed to material that contained misleading ·information.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty created by the words "may" and "if" might have resulted in the misled participants becoming more susceptible to the inaccurate information. According to Zaragoza and Lane (1994), the act of answering a misleading question leads participants to replay the original event and if the question was misleading, incorporate some of the inaccurate information into a memorial representation. Zaragoza and Lane's participants, knowing that they were to be presented with inaccuracies, may have been more certain about which details were inaccurate than the participants in the present study who may have been uncertain as to whether or not there were misleading questions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations